2006
DOI: 10.1007/s10705-005-1701-9
|View full text |Cite
|
Sign up to set email alerts
|

Synchronizing N Supply from Soil and Fertilizer and N Demand of Winter Wheat by an Improved Nmin Method

Abstract: Excessive nitrogen (N) fertilizer application and poor timing of N fertilizer application to winter wheat are common problems on the North China Plain. To study the possibilities of optimizing the timing and rate of N application, a field experiment was conducted from 1999 to 2001 in a suburb of Beijing. A control (no nitrogen) and two N fertilization strategies (conventional N application and optimized N fertilization) were designed to compare their effects on wheat growth, N nutrient status, grain yield and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
95
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(104 citation statements)
references
References 13 publications
6
95
1
2
Order By: Relevance
“…Development of fertiliser products capable of precise in-season nutrient supply (Chen et al, 2006 holds the promise of improving nutrient use efficiency and greater yields without increasing fertiliser use (Zhang et al, 2011). The ability to defer P supply demonstrated in the pot trial through the use of either SL or HT additions may be useful in achieving this goal, where crop uptake profiles often involve a greater nutrient requirement later in the season than at the beginning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Development of fertiliser products capable of precise in-season nutrient supply (Chen et al, 2006 holds the promise of improving nutrient use efficiency and greater yields without increasing fertiliser use (Zhang et al, 2011). The ability to defer P supply demonstrated in the pot trial through the use of either SL or HT additions may be useful in achieving this goal, where crop uptake profiles often involve a greater nutrient requirement later in the season than at the beginning.…”
Section: Discussionmentioning
confidence: 99%
“…By managing N fertiliser in a manner that ensured non-limiting N supply with minimum excess (and minimum losses) through in-season root zone N management. Chen et al (2006Chen et al ( , 2010 were able to almost double maize yields with no increase in fertiliser use (Zhang et al, 2011). In this management, total fertiliser N additions are divided into sub-applications that are applied throughout the growing season .…”
Section: Introductionmentioning
confidence: 99%
“…In 2006, China consumed 31 million tons of chemical nitrogen (N) fertilizer, accounting for about 32 percent of global N consumption (Heffer, 2009). Several studies have shown that in China, N-fertilizer use has been excessively used in grain production (Cai et al, 2002;Chen et al, 2006;Cui et al, 2008;Fan et al, 2007;Ma et al, 2008;Peng et al, 2002;Yan et al, 2012) and vegetable farming (Chen et al, 2004;He et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Several indices have been used to estimate soil N supply, such as alkaline hydrolyzable-N (Roberts et al 2011), nitrate (Cela et al 2013), soil mineral N (Chen et al 2006) and hydrolyzable amino sugar N (Khan et al 2001). Despite the fact that there are several indices, usage of each method has been limited, depending on numerous and complicated N-cycle processes.…”
Section: Introductionmentioning
confidence: 99%